(untitled) (International Journal of Engineering and Computer Science, 2015)
Symmetric symbol repeat (SSR) inter carrier interference (ICI) self cancellation scheme has proved to be a simple and convenient technique to reduce ICI caused by frequency offsets. It utilizes data allocation and combining of (1,-1) on two symmetrically placed subcarriers to mitigate the effect of ICI. However, the data allocation factors (1,-1) are not an optimum. In this paper, an optimum data allocation (1, -